Multicolor fluorescent glass ceramic, preparation method thereof, LED light-emitting device and LD light-emitting device

Through low-temperature sintering technology and high-temperature tube furnace sintering, the problems of complex and high cost of traditional fluorescent glass ceramics are solved, and the rapid preparation and mass production of multi-color fluorescent glass ceramics with high brightness and high thermal conductivity are achieved, which meets the needs of the Requirements for high brightness lighting applications.

CN119161104AInactive Publication Date: 2024-12-20NINGBO UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411555038.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing white LEDs have light decay and color bias problems in high-brightness lighting applications, and the preparation process of traditional fluorescent glass ceramics is complex and costly, and cannot meet the needs of high brightness and high thermal conductivity.

Method used

The multi-color fluorescent glass ceramics are prepared by low-temperature sintering technology. Through the mixing, defoaming and curing of PDMS and multi-color phosphors, combined with densified sintering of high-temperature tube furnaces, high physical and chemical stability is achieved at lower temperatures. and fluorescent glass ceramics with high thermal conductivity.

Benefits of technology

Multicolor quartz-based fluorescent glass ceramics with high quantum efficiency at low sintering temperatures are achieved, which simplifies the process, reduces costs, supports large-scale production, and maintains excellent luminous performance under high temperature and high humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161104A_ABST
    Figure CN119161104A_ABST
Patent Text Reader

Abstract

The invention provides multicolor fluorescent glass ceramic, a preparation method thereof, an LED light-emitting device and an LD light-emitting device, and relates to the technical field of light-emitting materials. The preparation method of the multicolor fluorescent glass ceramic specifically comprises the following steps: mixing PDMS and multicolor fluorescent powder raw materials, and uniformly stirring to obtain precursor slurry; sequentially carrying out defoaming treatment and curing treatment on the precursor slurry to obtain a fluorescent glass ceramic green body; and carrying out densification sintering on the fluorescent glass ceramic green body at 300-900 DEG C for 0.5-10 hours to obtain the multicolor fluorescent glass ceramic. Compared with other quartz-based fluorescent glass ceramic prepared through high-temperature sintering in the prior art, the compact fluorescent glass ceramic can be obtained only at a low sintering temperature, the preparation process is simpler, and large-scale and batch production can be achieved through lower manufacturing cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of luminescent materials, and in particular to a multicolor fluorescent glass ceramic and a preparation method thereof, an LED luminescent device and an LD luminescent device. Background Art

[0002] In recent years, blue LEDs have been widely used in combination with yellow phosphors to prepare fluorescent conversion white LEDs (pc-WLEDs) due to their many advantages such as low energy consumption, long life, and small size. This technical solution generally requires epoxy resin or silicone resin as packaging materials. However, such polymer materials have poor thermal conductivity (0.1–0.4 W / m / K) and heat resistance (less than 150°C), and the heat generated by the device cannot be effectively dissipated, resulting in light decay and color shift in pc-WLEDs. Therefore, traditional white LEDs are completely unable to meet the application requirements of fields such as searchlights, projection displays, and automotive headlights that require high-brightness lighting or displays.

[0003] At present, all-inorganic fluorescent converters that can withstand high-power LED and laser diode (LD) irradiation and have high thermal conductivity, including single crystals, transparent ceramics and glass ceramics, have been developed to replace traditional phosphors. Among them, single crystals (such as Chinese invention patents CN112080798A, CN100389504C) and transparent ceramics (such as Chinese invention patents CN111039660A, CN117049861A) have high thermal conductivity and excellent physical and chemical stability, but their preparation process is complex and the production cost is extremely high, which is not suitable for mass production. Glass ceramic fluorescent converters are becoming the research focus in the field of fluorescent conversion materials due to their high luminous efficiency, simple production process and low production cost. The main preparation method of fluorescent glass ceramics is to mix phosphors with multi-component low-melting-point glass powders in a certain proportion and then co-fire at low temperature (such as Chinese invention patent documents CN115432924A, CN116282937A, CN115893858A), but the physical and chemical stability of this type of glass is far inferior to that of quartz glass. Existing fluorescent glass ceramics based on quartz glass often require high-temperature melting preparation (such as Chinese invention patent documents CN109824246A and CN116947311A respectively mention that the preparation temperature of quartz glass is at least 1600°C). The high temperature of molten glass will cause the embedded phosphors to deteriorate, resulting in low luminous quantum efficiency.

[0004] Therefore, the invention of a quartz-based fluorescent glass ceramic that can be quickly prepared at a relatively low sintering temperature with high quantum efficiency and excellent physical and chemical stability has important application value in the field of high-brightness LED or LD lighting. Summary of the invention

[0005] In order to overcome the defects of the above-mentioned prior art, the present invention provides a multi-color fluorescent glass ceramic and a preparation method thereof, an LED light-emitting device and an LD light-emitting device, which can achieve the rapid preparation and mass production of multi-color quartz-based fluorescent glass ceramics with stable physical and chemical properties, high thermal conductivity and excellent luminescence performance only through low-temperature sintering.

[0006] The present invention provides a method for preparing multicolor fluorescent glass ceramics, and the preparation method specifically comprises the following steps: S1. Preparation of precursor slurry: PDMS and multi-color phosphor raw materials are mixed and stirred evenly to obtain a precursor slurry; S2. Curing: The precursor slurry obtained in step S1 is sequentially subjected to defoaming treatment and curing treatment to obtain a fluorescent glass ceramic body. The specific parameters of the curing treatment are as follows: a temperature of 100-200°C and a time of 1-10h; S3. Sintering: The fluorescent glass ceramic body obtained in step S2 is densified and sintered at 300-900° C. for 0.5-10 h to obtain a multicolor fluorescent glass ceramic.

[0007] Compared with the prior art, the present invention has the following advantages: 1. The sintering conditions in the preparation method of the present invention are milder, and the low sintering temperature can effectively inhibit the interface reaction between the glass matrix and the phosphor, so that the fluorescent glass ceramics have a higher quantum efficiency; 2. Compared with other high-temperature sintering methods to prepare quartz-based fluorescent glass ceramics, the present invention can obtain dense fluorescent glass ceramics only at a lower sintering temperature, and its preparation process is simpler. The lower manufacturing cost is also conducive to large-scale and batch production.

[0008] In a possible implementation manner, in step S1, the mass ratio of the multicolor phosphor raw material to PMDS is 1:(5-9), and the multicolor phosphor raw material is selected from YAG:Ce 3+ Yellow phosphor, LuAG:Ce 3+ Green phosphor and CASiN:Eu 2+ At least one of the red phosphors.

[0009] Among them, YAG:Ce 3+ The chemical formula can be expressed as (Y 1-x Ce x )3Al5O 12 , where x represents Ce 3+ Doping ratio. Ce 3+ Ions can emit yellow fluorescence under proper excitation, so it is a yellow phosphor; while LuAG:Ce 3+ The chemical formula can be written as (Lu 1-x Ce x )AlO4, where x represents Ce 3+The material can emit green fluorescence under appropriate excitation conditions. 2+ It is a nitride-based phosphor, where CASiN refers to Calcium Aluminum Silicon Nitride, and Eu 2+ Represents divalent europium ions. This phosphor can emit red fluorescence under appropriate excitation conditions. The above three phosphors are all commercially available.

[0010] In a possible implementation, in step S2, the defoaming treatment is performed in a vacuum device, and the parameters of the defoaming treatment are as follows: the vacuum degree is 133 Pa, and the time is 60-240 min.

[0011] Compared with the prior art, the present invention sets the degassing treatment conditions to a vacuum degree of 133 Pascals (Pa) and a treatment time of 60 to 240 minutes, which helps to remove air bubbles in the slurry and reduce product defects such as pores or unevenness caused by the presence of bubbles, thereby improving the quality of the finished product. Compared with the prior art, the curing process of the present invention controls the temperature between 100 and 200 degrees Celsius and lasts for 1 to 10 hours, which aims to allow the components in the slurry to undergo chemical or physical changes at a lower temperature, thereby forming a solid green body with preliminary structural strength.

[0012] In a possible implementation, in step S3, the densification sintering is performed in a high-temperature tube furnace with a vacuum degree of 0.1-100Pa.

[0013] Compared with the prior art, the present invention places the fluorescent glass-ceramic blank that has completed low-temperature solidification in a high-temperature tube furnace for densification sintering. This is because the high-temperature tube furnace can provide precise temperature control and a uniform heating environment, which is very important for ensuring the effectiveness of the sintering process and the quality of the final product; at the same time, the present invention adopts a high vacuum process in the densification sintering process, and the vacuum degree is set at 0.1 to 100 Pascals (Pa), mainly because the high vacuum environment can effectively reduce the impact of impurities in the air on the sintering process, especially prevent oxidation and other unnecessary chemical reactions, which is crucial for maintaining the purity and fluorescence properties of the material.

[0014] In a possible implementation, in step S3, the densification sintering is performed in a high-temperature tubular furnace under a protective atmosphere, and the protective atmosphere is selected from at least one of hydrogen, a mixture of nitrogen and hydrogen, a mixture of argon and hydrogen, and carbon monoxide.

[0015] Compared with the prior art, the present invention places the fluorescent glass-ceramic body that has completed low-temperature solidification in a high-temperature tube furnace for densification sintering, and during the sintering process, one or more protective atmospheres are used to prevent the material from reacting with oxygen in the air at high temperature, thereby affecting its performance.

[0016] In a possible implementation, the step S4 is also included. The multi-color fluorescent glass ceramic is ground and polished according to the designed size to finally obtain the multi-color fluorescent glass ceramic of the required size.

[0017] The second object of the present invention is to provide a multicolor fluorescent glass ceramic prepared by the above preparation method.

[0018] Compared with the prior art, the mother matrix of the multicolor fluorescent glass ceramics prepared by the present invention is pure quartz glass, which has very excellent physical and chemical stability and can withstand high-density blue light irradiation for a long time under high temperature and high humidity conditions without changing the luminescence performance.

[0019] The third object of the present invention is to provide an LED light-emitting device, comprising: a substrate, an LED chip and multi-color fluorescent glass ceramics, wherein the LED chip is arranged on the substrate, and the multi-color fluorescent glass ceramics is arranged on the top of the LED chip.

[0020] The fourth object of the present invention is to provide an LD light-emitting device, comprising: a substrate, an LD diode and multi-color fluorescent glass ceramics, wherein the LD diode is arranged on the substrate, and the multi-color fluorescent glass ceramics is arranged on the LD diode. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 XRD spectra of the fluorescent glass ceramics prepared in Example 1, Example 2 and Example 3 of the present invention; Figure 2 The excitation and emission spectra of the green fluorescent glass ceramics prepared in Example 1 of the present invention; Figure 3 The excitation and emission spectra of the yellow fluorescent glass ceramics prepared in Example 2 of the present invention; Figure 4 The excitation and emission spectra of the red fluorescent glass ceramics prepared in Example 3 of the present invention; Figure 5 The graph is a variation curve of the luminous flux of the fluorescent glass ceramics prepared in Example 1, Example 2 and Example 3 of the present invention under irradiation of a blue light LD as the laser power density increases; Figure 6 This is the electroluminescence spectrum of the multicolor fluorescent ceramic prepared in Example 8 of the present invention under the excitation of a blue LED chip. DETAILED DESCRIPTION

[0022] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0023] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0024] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0025] The technical effects of the present invention are described below in conjunction with specific embodiments.

[0026] Example 1

[0027] This embodiment provides a green fluorescent glass ceramic, which is prepared by the following preparation method: green fluorescent powder LuAG:Ce 3+ The precursor slurry is placed in a vacuum device and kept at 133Pa for 120 minutes to remove bubbles; after completing the above steps, the precursor slurry is poured into a mold of a specific shape with a thickness of 1mm, and then placed in a drying oven at a temperature of 150℃ for low-temperature curing for 3h to obtain a fluorescent glass-ceramic blank; the blank is placed in a high-temperature tubular furnace, slowly heated (1℃ / min) to 400℃, and densely sintered for 1h at a vacuum degree of 80Pa to obtain a large-sized quartz-based green fluorescent glass-ceramic, which can be cut and polished to obtain green fluorescent glass-ceramics of various sizes and shapes.

[0028] After testing, the internal quantum efficiency of the green fluorescent glass ceramic slice obtained in this embodiment can reach 98%.

[0029] Figure 1 The XRD spectrum of the green fluorescent glass ceramics prepared in this embodiment is shown. Figure 1 It can be seen that the fluorescent glass ceramic contains a cubic phase of LuAG and an amorphous phase of quartz glass. Figure 2 The excitation and emission spectra of the green fluorescent glass ceramics prepared in this embodiment are as follows: Figure 2 It can be seen that under the excitation of blue light of 420-470 nm, it emits green light with a peak wavelength of 520 nm. Figure 5 The graph shows the change of the luminous flux of the fluorescent glass ceramic prepared in this embodiment as the laser power density increases under the irradiation of blue light LD. Figure 5 It can be seen that the fluorescent glass ceramics prepared in this embodiment can withstand a power density of 21 W mm -2 High power blue laser irradiation.

[0030] Example 2

[0031] This embodiment provides a yellow fluorescent glass ceramic, which is prepared by the following preparation method: yellow fluorescent powder YAG:Ce 3+ Weigh the precursor slurry with PDMS at a weight ratio of 1:9, then mix the two and stir them magnetically to obtain a precursor slurry; place the precursor slurry in a vacuum device and keep it at 133Pa for 60 minutes to remove bubbles. After completing the above steps, pour the precursor slurry into a mold with a thickness of 1mm and a specific shape, and then place it in a drying oven at a temperature of 100℃ for low-temperature curing for 1h to obtain a fluorescent glass ceramic blank. Place the blank in a high-temperature tube furnace, slowly heat (1℃ / min) to 300℃, and densely sinter for 0.5h at a vacuum degree of 100Pa to obtain a large-sized quartz-based yellow fluorescent glass ceramic, and cut and polish it to obtain yellow fluorescent glass ceramics of various sizes and shapes. The internal quantum efficiency of the yellow fluorescent glass ceramic sheet obtained in this embodiment can reach 97%.

[0032] Figure 1 The XRD spectrum of the yellow fluorescent glass ceramics prepared in this embodiment is shown. Figure 1 It can be seen that the fluorescent glass ceramics prepared in this embodiment contain the cubic crystal phase of YAG and the amorphous phase of quartz glass. Figure 3 The excitation and emission spectra of the yellow fluorescent glass ceramics prepared in this embodiment are as follows: Figure 3 It can be seen that it emits yellow light with a peak wavelength of 535 nm under the excitation of blue light of 420-470 nm. The graph showing the change of the luminous flux of the fluorescent glass ceramic prepared in this embodiment with the increase of laser power density under the irradiation of blue light LD is shown. Figure 5 It can be seen that the fluorescent glass ceramics prepared in this embodiment can withstand a power density of 18 W mm -2 of blue laser irradiation.

[0033] Example 3

[0034] This embodiment provides a red fluorescent glass ceramic, which is prepared by the following preparation method: red fluorescent powder CASiN:Eu 2+Weigh the precursor slurry with PDMS at a weight ratio of 3:7, then mix the two and stir them magnetically to obtain a precursor slurry; put the precursor slurry into a vacuum device and keep it at 133Pa for 180 minutes to remove bubbles; after completing the above steps, pour the precursor slurry into a mold with a thickness of 3mm and a specific shape, and then place it in a drying oven at a temperature of 200℃ for low-temperature curing for 10h to obtain a fluorescent glass ceramic blank; put the blank into a high-temperature tube furnace, slowly heat (1℃ / min) to 700℃, and densely sinter for 5h at a vacuum degree of 10Pa to obtain a large-sized quartz-based red fluorescent glass ceramic, and cut and polish it to obtain red fluorescent glass ceramics of various sizes and shapes. The internal quantum efficiency of the red fluorescent glass ceramic sheet obtained in this embodiment can reach 95%.

[0035] Figure 1 The XRD spectrum of the red fluorescent glass ceramics prepared in this embodiment is shown. Figure 1 It can be seen that the fluorescent glass ceramic contains a crystalline phase of CASiN and an amorphous phase of quartz glass. Figure 4 The excitation and emission spectra of the red fluorescent glass ceramics prepared in this embodiment are as follows: Figure 4 It can be seen that under the excitation of blue light of 420-470 nm, it emits red light with a peak wavelength of 650 nm. Figure 5 The graph shows the change of the luminous flux of the fluorescent glass ceramic prepared in this embodiment as the laser power density increases under the irradiation of blue light LD. Figure 5 It can be seen that the fluorescent glass ceramics prepared in this embodiment can withstand a power density of 15 W mm -2 of blue laser irradiation.

[0036] Example 4

[0037] This embodiment provides a red fluorescent glass ceramic, which is prepared by the following preparation method: red fluorescent powder CASiN:Eu 2+Weigh the precursor slurry with PDMS at a weight ratio of 4:6, then mix the two and stir them magnetically to obtain a precursor slurry; put the precursor slurry into a vacuum device and keep it at 133Pa for 240 minutes to remove bubbles; after completing the above steps, pour the precursor slurry into a mold with a thickness of 5mm and a specific shape, and then place it in a drying oven at a temperature of 120℃ for low-temperature curing for 10h to obtain a fluorescent glass ceramic blank; put the fluorescent glass ceramic blank into a high-temperature tube furnace, slowly heat (1℃ / min) to 900℃, and densely sinter for 10h at a vacuum degree of 0.1Pa to obtain a large-sized quartz-based red fluorescent glass ceramic, and cut and polish it to obtain red fluorescent glass ceramics of various sizes and shapes. The internal quantum efficiency of the red fluorescent glass ceramic sheet obtained in this embodiment can reach 90%, and other luminescent properties are similar to those in Example 3.

[0038] Example 5

[0039] This embodiment provides a yellow fluorescent glass ceramic, which is prepared by the following preparation method: yellow fluorescent powder YAG:Ce 3+ Weigh the precursor slurry with PDMS at a weight ratio of 1:9, then mix the two and stir them magnetically to obtain a uniform mixed slurry. Place the precursor slurry in a vacuum device and keep it at 133Pa for 120 minutes to remove bubbles. After completing the above steps, pour the precursor slurry into a mold of a specific shape with a thickness of 10mm, and then place it in a drying oven at a temperature of 120°C for low-temperature curing for 3h to obtain a fluorescent glass ceramic blank. Place the blank in a high-temperature tube furnace, slowly heat (1°C / min) to 700°C under the condition of passing a reducing atmosphere (N2:H2=95:5), and densely sinter for 2h to obtain a large-sized quartz-based yellow fluorescent glass ceramic, and cut and polish it to obtain yellow fluorescent glass ceramics of various sizes and shapes. The internal quantum efficiency of the yellow fluorescent glass ceramic flakes obtained in this embodiment can reach 94%, and other luminescent properties are similar to those in Example 2.

[0040] Example 6

[0041] This embodiment provides a green fluorescent glass ceramic, which is prepared by the following preparation method: green fluorescent powder LuAG:Ce 3+Weigh the precursor slurry with PDMS in a weight ratio of 3:7, then mix the two and stir them magnetically to obtain a uniform mixed slurry. Place the precursor slurry in a vacuum device and keep it at 133Pa for 120 minutes to remove bubbles. After completing the above steps, pour the precursor slurry into a mold with a thickness of 20mm and a specific shape, and then place it under a 200W 400 nm purple light lamp for 0.5h to cure and form a fluorescent glass ceramic blank. Place the blank in a high-temperature tube furnace, slowly heat (1℃ / min) to 700℃ under the condition of passing a reducing atmosphere (N2:H2=95:5), and densely sinter for 2h to obtain a large-sized quartz-based green fluorescent glass ceramic, and cut and polish it to obtain green fluorescent glass ceramics of various sizes and shapes. The internal quantum efficiency of the green fluorescent glass ceramic sheet obtained in this embodiment can reach 95%, and other luminescent properties are similar to those in Example 1.

[0042] Example 7

[0043] The yellow and green phosphors and PDMS were weighed in a weight ratio of 4:6, and then the two were mixed and magnetically stirred to obtain a uniform mixed slurry. The precursor slurry was placed in a vacuum device and kept at 133Pa for 120 minutes to remove bubbles. After completing the above steps, the precursor slurry was poured into a mold of a specific shape with a thickness of 10mm, and then placed under a 200W 400 nm purple lamp for 0.5h for curing and molding to obtain a fluorescent glass ceramic blank. The blank was placed in a high-temperature tube furnace, slowly heated (1℃ / min) to 700℃ under the condition of passing a reducing atmosphere (N2:H2=95:5), and densely sintered for 2h to obtain a large-size quartz-based multi-color fluorescent glass ceramic, and cut and polished to obtain multi-color fluorescent glass ceramics of various sizes and shapes. The internal quantum efficiency of the multi-color fluorescent glass ceramic sheet obtained in this embodiment can reach 92%.

[0044] Example 8

[0045] The green and red phosphors are weighed separately with PDMS in a weight ratio of 3:7, and then the two are mixed and magnetically stirred to obtain a uniform mixed slurry. The precursor slurry is placed in a vacuumable device and kept at 133Pa for 240 minutes to remove bubbles. After completing the above steps, the precursor slurry is poured into a mold of a specific shape with a thickness of 20mm, and then placed in a drying oven at a temperature of 200℃ for low-temperature curing for 10h to obtain a fluorescent glass ceramic blank. The blank is placed in a high-temperature tube furnace, slowly heated (1℃ / min) to 800℃, and densely sintered for 10h at a vacuum degree of 0.1Pa to obtain a large-sized quartz-based multicolor fluorescent glass ceramic, which is cut and polished to obtain multicolor fluorescent glass ceramics of various sizes and shapes. The internal quantum efficiency of the multicolor fluorescent glass ceramic flakes obtained in this embodiment can reach 90%. Figure 6 The electroluminescence spectrum of the multicolor fluorescent glass ceramics prepared in this embodiment under the excitation of a blue LED chip is shown in FIG. Figure 6 It can be seen that this fluorescent glass-ceramic has a wide color gamut and a high color rendering index.

[0046] It can be seen from the above embodiments that the present invention realizes the rapid preparation and mass production of multi-color quartz-based fluorescent glass ceramics with stable physical and chemical properties, high thermal conductivity and excellent luminescence performance only by low-temperature sintering.

[0047] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A method for preparing multicolor fluorescent glass ceramics, characterized in that: The preparation method specifically comprises the following steps: S1. Preparation of precursor slurry: PDMS and multi-color phosphor raw materials are mixed and stirred evenly to obtain a precursor slurry; S2. Curing: The precursor slurry obtained in step S1 is sequentially subjected to defoaming treatment and curing treatment to obtain a fluorescent glass ceramic body. The specific parameters of the curing treatment are as follows: a temperature of 100-200°C and a time of 1-10h; S3. Sintering: The fluorescent glass ceramic body obtained in step S2 is densified and sintered at 300-900° C. for 0.5-10 h to obtain a multicolor fluorescent glass ceramic.

2. The method for preparing the multicolor fluorescent glass ceramic according to claim 1, characterized in that: In the step S1, the mass ratio of the multicolor phosphor raw material to PDMS is 1:(5-9), and the multicolor phosphor raw material is selected from YAG:Ce 3+ Yellow phosphor, LuAG:Ce 3+ Green phosphor and CASiN:Eu 2+ At least one of the red phosphors.

3. The method for preparing the multicolor fluorescent glass ceramic according to claim 1, characterized in that: In the step S2, the defoaming treatment is performed in a vacuum device, and the parameters of the defoaming treatment are as follows: the vacuum degree is 133 Pa, and the time is 60-240 min.

4. The method for preparing the multicolor fluorescent glass ceramic according to claim 1, characterized in that: In the step S3, the densification sintering is performed in a high-temperature tube furnace, and the vacuum degree is 0.1-100Pa.

5. The method for preparing the multicolor fluorescent glass ceramic according to claim 1, characterized in that: In the step S3, the densification sintering is performed in a high-temperature tubular furnace under a protective atmosphere, and the protective atmosphere is selected from at least one of hydrogen, a mixture of nitrogen and hydrogen, a mixture of argon and hydrogen, and carbon monoxide.

6. The method for preparing the multicolor fluorescent glass ceramic according to claim 1, characterized in that: The method also includes step S4. According to the designed size, the multi-color fluorescent glass ceramics are ground and polished to finally obtain the multi-color fluorescent glass ceramics of the required size.

7. A multicolor fluorescent glass ceramic, characterized in that: The method is prepared by any one of claims 1 to 6.

8. An LED lighting device, comprising: A substrate, an LED chip and the multi-color fluorescent glass ceramic as described in claim 7, characterized in that the LED chip is arranged on the substrate, and the multi-color fluorescent glass ceramic is arranged on the top of the LED chip.

9. An LD light emitting device, comprising: A substrate, an LD diode and the multi-color fluorescent glass ceramic according to claim 7, characterized in that the LD diode is arranged on the substrate, and the multi-color fluorescent glass ceramic is arranged on the LD diode.

Citation Information

Patent Citations

  • Porous silicon carbide fibers and preparation method thereof

    CN101876095A

  • Preparation method of 4D printing ceramic and ceramic piece

    CN115141014A

  • Preparation method of photocurable rare earth doped low-oxygen silicon carbide fiber

    CN117107397A

  • Small-particle-size high-brightness rare earth ion europium activated aluminate fluorescent powder as well as preparation method and application thereof

    CN117757468A